2012
DOI: 10.1021/ac300070t
|View full text |Cite
|
Sign up to set email alerts
|

Nanohole-Based Surface Plasmon Resonance Instruments with Improved Spectral Resolution Quantify a Broad Range of Antibody-Ligand Binding Kinetics

Abstract: We demonstrate an affordable low-noise SPR instrument based on extraordinary optical transmission (EOT) in metallic nanohole arrays and quantify a broad range of antibody-ligand binding kinetics with equilibrium dissociation constants ranging from 200 pM to 40 nM. This nanohole-based SPR instrument is straightforward to construct, align, and operate, since it is built around a standard microscope and a portable fiber-optic spectrometer. The measured refractive index resolution of this platform is 3.1 × 10−6 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 52 publications
2
65
1
1
Order By: Relevance
“…However, in previous work, our group compared kinetic rate constants and K D values obtained from a nanohole SPR instrument to those obtained from a commercial SPR instrument. 16 Antibodies binding to non-lipid antigens with known K D values ranging from 200 pM to 40 nM were examined. For all binding interactions we studied, the rate constants and K D values obtained with nanohole SPR were quite similar to those measured with a commercial Biacore 3000 system.…”
Section: Resultsmentioning
confidence: 99%
“…However, in previous work, our group compared kinetic rate constants and K D values obtained from a nanohole SPR instrument to those obtained from a commercial SPR instrument. 16 Antibodies binding to non-lipid antigens with known K D values ranging from 200 pM to 40 nM were examined. For all binding interactions we studied, the rate constants and K D values obtained with nanohole SPR were quite similar to those measured with a commercial Biacore 3000 system.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 The plasmonic nano-hole array is particularly suitable for integration into microfluidics, 45 enabling real-time measurement of antibody-ligand binding kinetics 46 and/or multiplexed detection. 47 For example, Pang et al demonstrated a high-performance, microfluidic nano-hole array with a refractive index sensitivity of 1520 nm/RIU based on sequential injection of ethylene glycol in water.…”
Section: Plasmonic Sensorsmentioning
confidence: 99%
“…Additionally, the refractive index sensitivity of gold nanorods is linearly proportional to the aspect ratio, facilitating its tunability [97]. Nanostructures of other shapes, including nanocubes [106][107][108][109], nanoshells [110][111][112], nanodiscs [113][114][115], nanotriangles [116,117], nanostars [118][119][120], nanobipyramids [121,122], nanorice [123,124], nanoholes [125,126], and nanocrescents [56,[127][128][129][130], have also been investigated and expanded to nanocubes and nanocuboids enclosed with concave surfaces (Fig. 1).…”
Section: Effect Of Nanoparticle Composition Size and Shape On Plasmomentioning
confidence: 99%